Interaction with comprehensible input and its impact on fourth graders’ critical thinking in the EFL classroom (2022)
Eng: The comprehensible input used in class can be useful in more ways than just as a tool to expose the students to the target language; it can also be used as a way to reinforce their critical thinking through different scenarios that they will face and understand through the input used in the classes. The objective with this research was to understand how the incorporation of this comprehensible input could enhance the critical thinking skills in fourth grade students from a private school in Tunja which only have had a limited contact with the English language. We picked Action Research as our type of study to develop our project using Observations, Students Artifacts and Teachers’ Documents (lesson plans) as our instruments for this research in order to have a more accurate idea of the situations that the students were facing. Contrary to the general belief of using only level appropriate input; when we expose students to the language through content that is more advanced it helps students not only to gain more vocabulary and have a general perception on how to use the language but also to be able to use their critical thinking skills to analyze the situations they see and how those situations can be connected to real life circumstances they might be facing.